Bridging the Gap: Pre-Service Teachers’ Realities of Technology Integration in the Digital Classroom - Silitonga, Lusia Maryani; Sri Suciati; Wiyaka; Entika Fani Prastikawati; Nur Cholifah (ETERNAL (English Teaching Journal), 2025)
In the digital era, integrating technology into education is essential for preparing future-ready educators. This qualitative case study explores how pre-service teachers experience and implement digital tools in instructional settings. It focuses on their successes, challenges, and the pedagogical strategies they employ. Drawing on the Technological Pedagogical Content Knowledge (TPACK) framework and experiential learning theory, the study involved 15 pre-service teachers from a university in Semarang. Data were collected through semi-structured interviews and classroom observations, and analyzed using thematic analysis. The findings reveal that pre-service teachers primarily used technology to manage classrooms and engage students—for example, using interactive platforms like Kahoot! to maintain attention and assess understanding in real time. These tools influenced student reactions and led teachers to adapt their instructional strategies dynamically. While digital tools were seen as effective for promoting engagement and understanding, participants faced challenges related to digital literacy, infrastructure limitations, and a lack of mentorship. Technology-based assessment and proactive engagement strategies were less frequently applied, highlighting a gap between theoretical training and classroom practice. The results suggest that teacher education programs should provide more hands-on, guided experiences, reflective practices, and institutional support to develop digital teaching competence. This study contributes to ongoing efforts to align teacher training with the realities of technology-enhanced learning environments